Drugs in sport
Drugs in Sport has been launched by the team that developed the Daily Dose and Substance Misuse websites. In addition to their interest in helping tackle the problems caused by drug and alcohol misuse, members of the team are also sports enthusiasts. The team is led by Professor David Clark of the Department of Psychology, University of Wales, Swansea. He is an internationally recognised scientist with 25 years research experience, who trained with Professor Arvid Carlsson, winner of the Nobel Prize for Medicine in 2000. David is Director of the WIRED, an initiative that aims to help individuals and communities tackle drug and alcohol misuse and the problems they cause. He is conducting a number of community-based projects on drug and alcohol misuse. Jim Young is the key content provider for the Drugs in Sport and Daily Dose websites. He has a background in hospital-based nursing, postgraduate medical research, and is currently working in the molecular biology laboratories at the University of Wales, Swansea. His penchant for locating relevant information has earned him the sobriquet Sniffer Dog.